2016
DOI: 10.1016/j.jep.2016.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical survey of medicinal plants used to manage High Blood Pressure and Type 2 Diabetes Mellitus in Bitterfontein, Western Cape Province, South Africa

Abstract: Medicinal plants are widely used by High Blood Pressure and Type 2 Diabetes Mellitus sufferers. They employ diverse plant species to manage both conditions. In addition, some sufferers often use prescribed allopathic medication, as well as medicinal plants, but at different intervals. Despite high usage the plants identified are not currently threatened (Red Data list status: least concern).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 80 publications
1
29
0
Order By: Relevance
“…The demographic information of selected informant’s data shows that males (55%) dominates in the traditional knowledge compared to 45% of females. Contrarily, other authors reported the females to dominate in the traditional knowledge [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The demographic information of selected informant’s data shows that males (55%) dominates in the traditional knowledge compared to 45% of females. Contrarily, other authors reported the females to dominate in the traditional knowledge [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This plant, among the other 29 Tulbaghia species, is endemic to southern Africa particularly SA (Eastern Cape, KZN, Limpopo) and Zimbabwe, with various indigenous applications. It is used as an aphrodisiac, as well as to treat sinus conditions, headaches, cough, colds, asthma, tuberculosis (pulmonary), intestinal worms, HTN, and cancer of the esophagus [24,27,29,30,33], owing to its numerous pharmacological and biological properties. Besides the fact that it possesses sulfur-containing compounds (e.g., alliin), showing much resemblance to Allium ursinum (Amaryllidaceae) Linn.…”
Section: Stangeria Eriopus (Kunze) Baillmentioning
confidence: 99%
“…Plants have been used by millions of people as a source of food and for medicinal purposes for thousands of years [2,5]. An estimated 80% of the world's population and 80% of black South Africans still rely on traditional medicine for their primary health care needs [6]. Traditional medicine has not only gained popularity due to its effectiveness against diseases but because sometimes it is the only therapy that is available in rural areas in the context of developing countries [7].…”
Section: Introductionmentioning
confidence: 99%